ANALISIS KEMAMPUAN LITERASI MATEMATIS DALAM MENYELESAIKAN SOAL AKM DITINJAU DARI GAYA BELAJAR - Nadia Octavia Trisnaningtyas; Rita Pramujiyanti Khotimah (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
Based on the results of PISA 2018, mathematical literacy in Indonesia is low. Mathematical literacy skills are important for every student. One of the government's ways to improve mathematical literacy is with the National Assessment, which includes literacy and numeracy AKM. While each student has a different way of learning. Based on these problems, see the extent to which students' mathematical literacy skills in solving AKM questions with differences in student learning styles. This study expects to depict understudies' mathematical literacy skills in settling AKM type inquiries regarding learning styles. The technique utilized in this research is qualitative. The examination subjects comprosed of 3 students understudies of class X MIPA 4 SMAN 3 Taruna Angkasa with the classes of visual, auditory and kinesthetic learning styles. The instruments utilized in the review were a learning style poll, a mathematical literacy test and an interview. That’s what the outcomes showed: 1) subjects with visual learning styles met the sign of communication, mathematics, picking strategies, utilizing task and image language, formal language and specialized language; 2) subjects with auditory learning styles have met the marks of communication, math, picking techniques, utilization of activities and image language, formal language and specialized language and endlessly thinking; 3) subjects with kinesthetic learning styles just satisfy the marks of communication, math and picking stechniques.